Survey Kepuasan Pelayanan Publik Di Kantor Kelurahan Gunung Lengkuas Kecamatan Bintan Timur - Apriyani Fadhilah; Novi Winarti; Yudhanto Satyagraha Adiputra (Lembaga Pengembangan Kinerja Dosen, 2024)
The Gunung Lengkuas Village Office serves the community and public services in general. As we know, the task of the sub-district government is to support and assist the government in providing public services in the sub-district in its activities in accordance with its duties and responsibilities, providing facilities, directing administration, implementing service systems, and so on. However, there are several problems in public services at the Gunung Lengkuas District office, where there are several complaints submitted by the public, including the behavior of officers such as employee discipline, handling of complaints that are not followed up and so on. Therefore, this research aims to measure the level of community satisfaction in Gunung Lengkuas Village, East Bintan District. The method in this research uses quantitative descriptive methods. The sampling technique used was proportional stratified random sampling. In accordance with PAN Ministerial Decree No.14 of 2017, there are 9 indicators for community satisfaction surveys, namely requirements, system mechanisms and procedures, completion time, costs, product specifications, types of services, implementer competence, implementer behavior, complaint handling. , suggestions and input as well as facilities and infrastructure. The results of the research show that the survey score for community satisfaction with services at the Gunung Lengkuas Village office, East Bintan District, is 74.8 in the Bad category. The indicator with the highest index value with an average IKM value of 95 is costs and the indicator with the lowest index value with an average IKM value of 1.5 is facilities and infrastructure in the question of the existence of a lactation room.